1821 N.J. Laws 370-71 - (:unkn) unknown (My University, 1798)
An Act respecting slaves: Prohibited "any negro or other slave" from hunting or carrying a gun on the first day of the week, or Sunday subject to imprisonment.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES